Pengembangan Media Pembelajaran Digital untuk Internalisasi Nilai Moderasi Beragama pada PAUD di Wonosobo - Hidayatu Munawaroh (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2025)
This research aims to develop digital learning media oriented towards internalizing the value of religious moderation for early childhood in Wonosobo Regency. In the context of early childhood education (PAUD), religious moderation is an important aspect to form an attitude of tolerance, respect for differences, and instill the values of togetherness from an early age. The research method used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observations, interviews, and questionnaires involving PAUD educators, education experts, and parents of students. The results showed that the digital learning media developed was able to improve children's understanding of the concept of religious moderation through an interactive, visual, and educational game-based approach. The implementation of this media in several PAUD institutions in Wonosobo received positive responses from educators and parents, who considered that the media was effective in helping children understand the values of togetherness, tolerance, and mutual respect in diversity. This research recommends the integration of digital media based on religious moderation in the PAUD curriculum as well as training for educators to optimize its use in the learning process.